Hazard Analysis Critical Control Points (HACCP) Principle 6: Establish Verification Procedures - Ronald H. Schmidt; Debby L. Newslow (EDIS)
FSHN07-07, a 7-page fact sheet by Ronald H. Schmidt and Debby L. Newslow, describes the final HACCP principle, which consists of establishing verification procedures for the entire plan and ensuring that the system is operating correctly in accordance with the plan. Published by the UF Department of Food Science and Human Nutrition, August 2007.